PARTISIPASI MASYARAKAT PETANI PISANG MAS KIRANA DALAM PROSES PENGEMBANGAN KAWASAN AGROPOLITAN SEROJA KABUPATEN LUMAJANG - , YUYUN QOMARIYAH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Spatial Planning in Rural Areas was regulated in Spatial Planning Law No. 26 of 2007 which arranged in the form of agropolitan spatial planning. The development of agropolitan area consist of three concepts there are social change, spatial (geography), and the political community. There is a development policies of East Java Province Government in development of Agropolitan Areas which is followed up by Local Government of Lumajang Region with develop Seroja Agropolitan Area that cannot be separated from community participation, especially the participation of Mas Kirana banana farmers. The aim of this research are for determine the form of community participation of Mas Kirana banana farmers in the development process of Seroja Agropolitan Area